ANALISIS UNSUR ITIKAD BAIK PADA MEREK NAMA ORANG TERKENAL DALAM PASAL 21 UNDANG – UNDANG NOMOR 20 TAHUN 2016 TENTANG MEREK DAN INDIKASI GEOGRAFIS (STUDI KASUS: PUTUSAN MAHKAMAH AGUNG NOMOR 48/PDT.SUS/MEREK/2018/PN NIAGA JKT.PST) - Iqbal Akbar Mandiri; Simona Bustani (Jurnal Hukum Adigama, 2020)
Based on the related trademark dispute that occurred in Indonesia and which the author will use as research material is the Supreme Court's Decision Number: 48 / Pdt.Sus / Trademark / 2018 / PN.Niaga.Jkt.Pst which checks and decides on the BENSU brand dispute. The Plaintiff's trademark is none other than the impact of public attention on the Plaintiff with the word BENSU attached to the Trademark, and therefore the Plaintiff has objected to the Plaintiff's registered trademark thereby making public opinion "as if" it was the Plaintiff's property. Based on the contents in this thesis, there are problems as to how the application of good faith elements to the famous brand BENSU in the Supreme Court's decision Number: 48 / pdt.SUS / Trademark / 2018 / PN.JKT.PST and whether the decision is in accordance with applicable laws The following are the following implementing regulations. The research method in this thesis is divided into 3: the type of research which uses normative or doctrinal research, that is, the research provides a systematic explanation of the rules governing a category, the nature of research which uses the normative nature of practical and prescriptive, types and techniques writing there are primary legal materials, secondary legal materials, tertiary legal materials.